2014
DOI: 10.5596/c14-023
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Usability Study to Test the Redesign of the Health Sciences Library Web Page

Abstract: N/A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Other usability studies have indicated that participants had difficulty recognizing what single search boxes actually searched (Williams and Foster, 2011; Johnson, 2013) and that users often fall back on familiar patterns from previous library website experiences (Wilkinson, 2009; Lemieux and Powelson, 2014).…”
mentioning
confidence: 99%
“…Other usability studies have indicated that participants had difficulty recognizing what single search boxes actually searched (Williams and Foster, 2011; Johnson, 2013) and that users often fall back on familiar patterns from previous library website experiences (Wilkinson, 2009; Lemieux and Powelson, 2014).…”
mentioning
confidence: 99%